Exploring The Benefits And Types Of Vertical Jump Training On Volleyball Smash Technique: Literature Review - Afis, Firdaus Al Ridha; Apriani, Leni (Indonesian Journal of Sport Management, 2025)
Study This explore benefits and effectiveness Vertical jump training against Smash technique in volleyball​ based on review literature. Ability leap optimal vertical is very important for volleyball player​ For increase height and strength in perform an effective smash. Various method exercise such as Squat Jump, Hurdle Jump, Barrier Jump, Knee Tuck Jump, Leg Press, and Jump Frog has proven increase strength muscle legs, power explosive, balance, and stability moment landed. This literature review show that combination exercise plyometrics and training burden can in a way significant increase performance leap vertical and smash effectiveness. Therefore Therefore, a structured and consistent exercise program is highly recommended. for volleyball athlete​ For increase their smash technique.